Tradisi Jum’at Kliwon Keliling Kampung: Studi kasus desa Tanjung Belit kecamatan Siak Kecil kabupaten Bengkalis - Zulfila, Zulfila (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
The Ratib Jum’at Kliwon tradition in Tanjung Belit Village is a religious and cultural practice that integrates Islamic values with local wisdom. This tradition plays a significant role in the spiritual, social, and cultural life of the community. It serves as a medium to strengthen the belief in monotheism (tauhid), encourage spiritual reflection, and promote repentance among community members. Socially, the tradition functions as a means of fostering solidarity, enhancing social cohesion, and maintaining communal harmony. Moreover, it contributes to the preservation of cultural heritage by harmonizing Islamic teachings with indigenous traditions. This study uses a qualitative approach through interviews and observations, focusing on the implementation, meaning, and social impacts of the Ratib Jum’at Kliwon tradition. The findings highlight that the tradition remains a vital part of community identity and resilience in the face of social changes.